IMPLIKASI ETIS MENGIKUTI KRISTUS MENURUT YOHANES DAN PAULUS - Pabubung, Michael Reskiantio (Jurnal Euntes, 2023)
Following Christ is a conscious choice made by Christian believers but it also has consequences in everyday life. Living in the world requires a set of guidelines like a corridor for acting properly with the aim of helping others and gaining personal meaning in life. This guideline is an ethics of life inspired by the prime source of faith and morals, namely the Holy Bible. Through qualitative research using narrative analysis techniques and limitations on the New Testament, this research analyzes writings related to John and Paul to gain ethical insights. John offers an ethic of radical love, while Paul offers an ethic of wisdom guided by the Holy Spirit. These two ethics become powerful when synergized with each other, especially in pastoral and catechesis.